2016
DOI: 10.3390/metabo6040030
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Method for Untargeted Metabolomics Analysis of MDA-MB-231 Breast Cancer Cells

Abstract: Cancer cells often have dysregulated metabolism, which is largely characterized by the Warburg effect—an increase in glycolytic activity at the expense of oxidative phosphorylation—and increased glutamine utilization. Modern metabolomics tools offer an efficient means to investigate metabolism in cancer cells. Currently, a number of protocols have been described for harvesting adherent cells for metabolomics analysis, but the techniques vary greatly and they lack specificity to particular cancer cell lines wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 48 publications
(56 reference statements)
1
50
0
Order By: Relevance
“…Glucose was only present when cells were incubated with Glu-Gd, added in the PBS solution. Peterson et al (2016), demonstrated that c231 incorporates glucose into the glycolytic pathways (GP) and shows that the GP was highly active at 60 min Glu incubation (Peterson et al, 2016). Our data showed similar time Gd-Glu uptakes, at 30 and 50 min, in comparison to Peterson and cols information.…”
Section: Discussionsupporting
confidence: 64%
“…Glucose was only present when cells were incubated with Glu-Gd, added in the PBS solution. Peterson et al (2016), demonstrated that c231 incorporates glucose into the glycolytic pathways (GP) and shows that the GP was highly active at 60 min Glu incubation (Peterson et al, 2016). Our data showed similar time Gd-Glu uptakes, at 30 and 50 min, in comparison to Peterson and cols information.…”
Section: Discussionsupporting
confidence: 64%
“…Glutamate and glutamine denote a group of glucogenic amino acids that features many biological functions. These are considered to be very important for cell function maintenance and promotion, being glutamine an important metabolic precursor in rapidly-dividing cells [23]. Cell demands for glutamine and glutamate are enormous during severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…The obtention of samples from extracellular media is straightforward and requires a single centrifugation step of culture supernatants to remove cells and debris. On the contrary, numerous protocols aimed at the extraction of metabolites from biological matrices have been developed for NMR and MS analyses, some of which have been specifically tuned for cell cultures [ 49 , 51 , 52 , 56 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. These protocols are quite similar in principle for both analytical platforms but suit individual requirements such as avoiding high concentrations of protonated solvent molecules as concerns NMR profiling.…”
Section: Metabolic Phenotyping Of Cell Culture Metabolism: Analytimentioning
confidence: 99%